Erosion Dynamics of Cultivated Kelp, Saccharina latissima, and Implications for Environmental Management and Carbon Sequestration - Fieler, Reinhold; Greenacre, Michael; Matsson, Sanna; Neves, Luiza; Forbord, Silje; Hancke, Kasper (Frontiers in Marine Science, 2021)
A growing trend of interest for the cultivation of kelp is driven by predictions for high global demands of important commodities, which require the development of alternative supplies of natural resources. In this study the dynamics of loss of biomass from cultivated Saccharina latissima were studied from February to August 2018 at two kelp farms in Northern (69°45.26′N/019°02.18′E) and in Mid-Norway (63°42.28′N/08°52.23′E). Kelp fronds at each farm were individually followed throughout the growing season. Sectional regression was applied for conversion of measured frond lengths to estimated dry weights. The study shows that between 40 and 100% of all individuals in the studied kelp population constantly eroded slightly from their distal ends. However, until June the accumulated loss was only 8% of produced dry weight. Due to dislodgement of whole sporophytes this picture changed in July and August to heavy losses in Mid-Norway. Thus, the overall losses of kelp in terms of accumulated dry weight were only 8–13% of the gross growth until harvest in June in Mid-Norway and August in Northern Norway. Losses increased significantly in Mid-Norway during July and reached 49.4% of the annual production in August. The rates of losses were separated into specific erosion and dislodgement rates. Erosion rates over the whole experimental period for the two sites were not significantly different, while differences in dislodgement rates between farm sites proved to be highly significant. The exported annual amount of carbon was estimated on the basis of lost and measured carbon content in the tissue. From these data a scenario was built for a commercial Norwegian kelp farm growing S. latissima showing a carbon export of 63–88 g C m–2y–1. This is eight times less than has been reported from scenarios for kelp farms in China. This study confirms that optimal timing of harvest is the most important management tool for avoidance of heavy losses from kelp farms. In conclusion, an industry with early harvest will likely have a low carbon export, while a late-harvested bulk production could export four to six times as much carbon with an increased potential for carbon sequestration.